2015
DOI: 10.1111/ijfs.12955
|View full text |Cite
|
Sign up to set email alerts
|

Smoking and polyphenols’ addition to improve freshwater mullet (Mugil cephalus) fillets’ quality attributes during refrigerated storage

Abstract: Summary The combined effects of hot smoking and added quince polyphenol (0.8% and 1.6% v/w) on the quality attributes of mullet (Mugil cephalus) fillets were evaluated. Biochemical parameters that were monitored in the fillets during 75 days of storage (4 ± 1 °C) included trimethylamine (TMA‐N), volatile basic nitrogen (TVB‐N), fatty acids and amino acids. Data were submitted to principal component analysis (PCA) which revealed that the smoking process combined with polyphenols’ treatment was negatively correl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
20
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 15 publications
(25 citation statements)
references
References 39 publications
4
20
1
Order By: Relevance
“…Fresh thin-lipped grey mullet fillets showed initial low levels of TMA and TVB content (1.27±0.36 mg N/100 g and 9.96±0.74 mg N/100 g respectively) indicating the good quality of the product, These values are similar to initial values of the freshwater mullet M. cephalus reported in previous study [11]. However, these values are lower than values reported in other studies for marine M. cephalus [43].…”
Section: Biochemical Parameters Variations In Fresh and Smoked Filletsupporting
confidence: 82%
See 4 more Smart Citations
“…Fresh thin-lipped grey mullet fillets showed initial low levels of TMA and TVB content (1.27±0.36 mg N/100 g and 9.96±0.74 mg N/100 g respectively) indicating the good quality of the product, These values are similar to initial values of the freshwater mullet M. cephalus reported in previous study [11]. However, these values are lower than values reported in other studies for marine M. cephalus [43].…”
Section: Biochemical Parameters Variations In Fresh and Smoked Filletsupporting
confidence: 82%
“…Such difference may be due to fish origin with different environmental conditions [51]. The content of polyunsaturated fatty acids n-3, DHA C22: 6n-3 is similar (0.70%) with value reported in previous study for freshwater mullet [11], EPA C20:5n-3 meanwhile remains at fairly moderate (1.80±0.01 %). Similarly, Khitouni, et al [50] reported a moderate level of EPA in fresh golden grey mullet captured in the summer.…”
Section: Determination Of Fatty Acid Compositionsupporting
confidence: 77%
See 3 more Smart Citations